Gating-dependent terahertz study of single layer graphene - Sabrina Jumadi (2014)
In this thesis, we investigated on the properties of Macor as a sample holder for gating and temperature-dependent measurements and found that the lowest temperature possible is at 55 K. Also, only data at the range of 0.3 THz to 2.8 THz is reliable based on the transmittance measurements when the sample holder is empty and in vacuum. Prior to the measurements done on graphene, we have measured the complex refractive index of p-doped silicon which was used as a substrate on graphene. Terahertz time-domain spectroscopy was employed on a back-gate graphene field-effect transistor for gate voltages between -35 V to 35 V and further measurements have shown that only measurements done from -25 V to 15 V can be trusted. We observed the decrease in carrier density and scattering rate as the gate volt- age increases leading us to an explanation that as the gate voltage increases, it moves closer to Dirac point. Further work can be done to investigate the temperature dependence on gated graphene other types of gating could also be done to find out the change in carrier dynamics in graphene.